Das Lied von der Erde. - Antmen, Ahu; Block, René; Bärthel, Regina; Chan-Dong, Kim; Glaser, Martin; Grynsztejn, Madeleine; Kellner, Clive; Latos-Valier, Paula; Llanes, Llilian; Raspail, Thierry (Kassel : Museum Fridericianum, 2000)
Ballet, Elisabeth ; Brecht, George ; Breitz, Candice ; Buren, Daniel ; Choi, Jeong Hwa ; Chung, Seoyoung ; Croft, Brenda L. ; Deacon, Destiny ; Frize, Bernard ; Gomes, Fernanda ; Kaprow, Allan ; Kcho ; Kentridge, William ; Kim, Young-Jin ; Laing, Rosemary ; Langa, Moshekwa ; Lee, Soo-Kyung ; Macpherson, Robert ; Meireles, Cildo ; Mofokeng, Santu ; Morris, Sarah ; Özseçen, Ebru ; Onur, Füsun ; Perez Bravo, Marta Maria ; Piccinini, Patricia ; Sangar, Bülent ; Tenger, Hale ; Tyndall, Peter ; Whang Inkie
Das Lied von der Erde, Museum Fridericianum, Kassel, 10. Juni bis 3. Oktober 2000
biog. p. 123-129
Duits
Engels
kunstcatalogus